2007
DOI: 10.1167/iovs.07-0572
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Mapping of Myopia Susceptibility Loci

Abstract: This is the first study to assess for linkage in a secondary myopia twin cohort and highlights the problems associated with applying linkage results from complex traits to the other populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…70 In contrast, Schache and colleagues did not report linkage to this site in their study of 233 adult dizygotic Australian twin pairs. 64 It is possible that the twins in this study are in some way selectively different from the twins in Hammond's study. Such lack of consistency is not uncommon in genetic studies of complex traits.…”
Section: Geneticsmentioning
confidence: 80%
See 1 more Smart Citation
“…70 In contrast, Schache and colleagues did not report linkage to this site in their study of 233 adult dizygotic Australian twin pairs. 64 It is possible that the twins in this study are in some way selectively different from the twins in Hammond's study. Such lack of consistency is not uncommon in genetic studies of complex traits.…”
Section: Geneticsmentioning
confidence: 80%
“…[57][58][59][60] Some of the regions associated with high myopia have been mapped to chromosomes 18p11.3 (MYP2), 61 12q21 to 23 (MYP3), 62 17q21 to 22 (MYP5) 63 and to other sites. 57,59,[62][63][64][65][66][67][68] Moderate myopia has been mapped to 22q13 69 and 8p23. 70,71 Simpson and colleagues examined the association of PAX 6 and SOX2 with refraction in a British cohort.…”
Section: Geneticsmentioning
confidence: 99%
“…24 The first twin-based sib-pair linkage study exploring ocular refraction/ myopia from the TwinsUK cohort showed evidence for linkage for four loci (MYP7-10) with spherical equivalent as the continuous outcome variable. 25 Other twin linkage studies in ocular diseases include the GEM study's attempt to replicate these myopia linkage findings; 26 the Australian Twin Eye Study of axial length, 27 which showed significant evidence for linkage on chromosome 5q24, and the study by Sun et al (2009) 28 from the same group, which provided suggestive evidence for linkage on chromosome 2p14 with retinal vascular calibre (a risk factor for microvascular disease). Although linkage studies successfully identified novel loci for several eye traits, they have been limited by lack of replication, a common problem in linkage studies of many complex traits and diseases.…”
Section: Linkage Studiesmentioning
confidence: 99%
“…More and more research into genetic factors of myopia give rise to its importance, with improved understanding of its biological mechanism (2,(13)(14)(15)(16)(17)(18). The association study of candidate genes and loci has been evaluated and the available evidence suggests the involvement of certain genes and loci in myopia in different ethnic populations (19)(20)(21)(22)(23)(24)(25)(26).…”
Section: Introductionmentioning
confidence: 99%